2016
DOI: 10.1111/eos.12289
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dentin pretreatment with synthetic hydroxyapatite application on the bond strength of fiber posts luted with 10‐methacryloyloxydecyl dihydrogen phosphate‐containing luting systems

Abstract: The aim of this in vitro study was evaluate the effect of application of synthetic hydroxyapatite on fiber post bond strength to radicular dentine. Forty, single-root teeth were endodontically treated and an 8 mm post space was prepared. Specimens were randomly placed in four groups (n = 10 in each) and treated using the following fiber post luting procedures: group 1, 17% EDTA + Panavia SA; group 2, 17% EDTA + Teethmate Desensitizer + Panavia SA; group 3, All-Bond Universal + Duo-Link Universal; and group 4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…In agreement with these results, a previous study reported the formation of an apatite layer at the interface and tooth surface, when a modified composition (with similar nHA/E‐glass fibres) was used as a restorative material in a coronal tooth cavity (Syed et al, 2020). Similar findings have been reported, that is, pre‐treatment with synthetic hydroxyapatite revealed a significant improvement in the bond strength of fibre posts when used with 10‐methacryloyloxydecyl dihydrogen phosphate‐containing cement (Scotti et al, 2016). It is anticipated that leaching of calcium and phosphate ions from nHA can form an apatite layer within the structure as described earlier by our group (Saleem et al, 2021; Syed et al, 2020), and it can also improve the mineral content of the post space by altering the smear layer (Scotti et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In agreement with these results, a previous study reported the formation of an apatite layer at the interface and tooth surface, when a modified composition (with similar nHA/E‐glass fibres) was used as a restorative material in a coronal tooth cavity (Syed et al, 2020). Similar findings have been reported, that is, pre‐treatment with synthetic hydroxyapatite revealed a significant improvement in the bond strength of fibre posts when used with 10‐methacryloyloxydecyl dihydrogen phosphate‐containing cement (Scotti et al, 2016). It is anticipated that leaching of calcium and phosphate ions from nHA can form an apatite layer within the structure as described earlier by our group (Saleem et al, 2021; Syed et al, 2020), and it can also improve the mineral content of the post space by altering the smear layer (Scotti et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…Similar findings have been reported, that is, pre‐treatment with synthetic hydroxyapatite revealed a significant improvement in the bond strength of fibre posts when used with 10‐methacryloyloxydecyl dihydrogen phosphate‐containing cement (Scotti et al, 2016). It is anticipated that leaching of calcium and phosphate ions from nHA can form an apatite layer within the structure as described earlier by our group (Saleem et al, 2021; Syed et al, 2020), and it can also improve the mineral content of the post space by altering the smear layer (Scotti et al, 2016). According to the results of this study, the eS post demonstrated the lowest bond strength values.…”
Section: Discussionsupporting
confidence: 83%
“…There are recent interesting suggestions of dentin conditioning with boric acid, H 3 BO 3 [26] to remove the smear layer. On the other hand, the use of synthetic hydroxyapatite might be helpful for enhancing chemical bonding [27] when using self-adhesive resin composite cements. In addition, it may be thought that the poor bond strength may be due to the high C factor, which is the ratio of the bonded surfaces to the unbonded surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…After dentin substrate etching, these cements are able to infiltrate within the dentinal tubules and the demineralized collagen fibril network, bonding to the dentin by micro-mechanical retention (109,110). When adhesive cements containing functional monomers such as 10methacryloyloxidecyl dihydrogen phosphate (10-MDP) are used, chemical bonding is also achieved due to the strong ionic bonds established between the adhesive and the calcium ions of the hydroxyapatite crystals (110,111).…”
Section: Bioactive Materials For Cementation Of Indirect Restorationsmentioning
confidence: 99%